Italy’s foreign trade in 1950: January-September - PIETRANERA, G. (PSL Quarterly Review, 2014)
The survey analyses, with the help of detailed statistical elaborations, the principal characteristics of the currents of Italy’s international trade during the first nine months of 1950. The period under consideration is of special interest as the consequences of the devaluations of September 1949 were making themselves felt and the effects of the “liberalisation policy” in inter-european exchanges were taking shape. It coincided, moreover, with the period in which the passage from a buyer’s to a seller’s market seemed to be acquiring consistency, but which was again to be reversed by the Korean war. JEL: F10, F13